Government Subsidies and Fiscal Burdens for Home-based Elderly Care Services - Sun, Yiwan; Qin, Shaopeng (Transactions on Economics, Business and Management Research, 2023)
Based on the number of older people of different ages, genders and health conditions from 2021 to 2050, this paper measures the scale of demand for China’s home-based elderly care services. We simulated government subsidies’ scale and fiscal burden under nine scenarios with different subsidy standards and coverage processes. The results show that the policy coverage and subsidy standards significantly affect the government subsidies and fiscal burdens of home-based elderly care services. To balance fiscal sustainability, China should start the procedure with "low standard with small coverage" and gradually transfer to "high standard with wide coverage."